(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article endeavors to explore the linguistic construct of homonymy, providing a comprehensive scrutiny of its fundamental characteristics, which include definitions, classifications, and its crucial role in the analysis of language.